2018
DOI: 10.1515/jomb-2017-0062
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Serum Levels of the Adipocytokine Chemerin in Colorectal Cancer Patients

Abstract: SummaryBackground Colorectal cancer (CRC) is one of the most common cancers worldwide. The tumor microenvironment is very important for determining cancer cell growth and spreading. Chemerin, a newly identified adipokine secreted by adipose tissue, is known to be associated with obesity, metabolic syndrome, and insulin resistance. The present study was carried out to investigate the association between serum levels of chemerin and colorectal cancer.MethodsThirty-two patients with colorectal cancer aged 57.6±6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…In our study, patients with a higher chemerin level had a 3-fold increased risk of developing CRA, and a significant positive correlation was observed between serum chemerin level and the number of CRA, which is a precancerous lesion of CRC [41]. Our results are consistent with those of recent reports showing that chemerin is associated with the development of CRC [26,42]. Although we could not elucidate the mechanisms underlying the role of chemerin in the development of CRA, these findings indicate that chemerin might have a potential role in the progression of colorectal tumorigenesis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, patients with a higher chemerin level had a 3-fold increased risk of developing CRA, and a significant positive correlation was observed between serum chemerin level and the number of CRA, which is a precancerous lesion of CRC [41]. Our results are consistent with those of recent reports showing that chemerin is associated with the development of CRC [26,42]. Although we could not elucidate the mechanisms underlying the role of chemerin in the development of CRA, these findings indicate that chemerin might have a potential role in the progression of colorectal tumorigenesis.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, chemerin may be a potential biomarker of malignant diseases, such as gastric cancer [25]. A recent report has shown that the circulating chemerin levels of patients with CRC are higher, and it gradually increases with the progression of TNM stage [26]. However, only a few reports have elucidated the re-lationship between chemerin levels and CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Among the early diagnostic tools that have become available in recent years, serum chemerin levels have been identified as an effective biomarker for colorectal cancer. A study in 2018 compared 32 colorectal cancer patients with sex, BMI, and age matched healthy volunteers and reported that chemerin was significantly upregulated in serum of colorectal cancer patients, increasing with higher tumor stage progression ( 58 ). The area under the receiver operating characteristic (ROC) curve for serum chemerin levels was 1, with a sensitivity and specificity of 100% ( 58 ).…”
Section: Cancersmentioning
confidence: 99%
“…A study in 2018 compared 32 colorectal cancer patients with sex, BMI, and age matched healthy volunteers and reported that chemerin was significantly upregulated in serum of colorectal cancer patients, increasing with higher tumor stage progression ( 58 ). The area under the receiver operating characteristic (ROC) curve for serum chemerin levels was 1, with a sensitivity and specificity of 100% ( 58 ). The results clearly indicated that serum chemerin could be an effective biomarker for colorectal cancer and stage progression.…”
Section: Cancersmentioning
confidence: 99%
“…Recent studies indicated anti-inflammatory effects of vaspin and omentin in obesity and insulin resistance conditions (20)(21)(22). Vaspin, a member of the serine protease inhibitor family, is an insulin-sensitizing adipokine which upregulated in metabolic diseases to compensate insulin resistance and inflammatory complication and furthermore may play an in hibition role in brosis development and progression (23,24). This observation suggested the possible contribution of vaspin in liver brogenesis (25).…”
Section: Discussionmentioning
confidence: 96%